Pengembangan Aplikasi CareCouns Berbasis Profil Pelajar Pancasila untuk Pencegahan Pergaulan Bebas - Mustika, Tri Afriyanti; Abdul Saman; Abdullah Pandang (Technocouns: Journal of Technology in Guidance and Counseling, 2025)
ABSTRACT. This research aims to develop the CareCouns application based on Pancasila Student Profiles as a preventive measure against free association among students at UPT SPF SMPN 48 Makassar. The study employed the Research and Development (R&D) method by Borg and Gall, modified to the second revision stage. Data were collected through questionnaires and in-depth interviews, analyzed using quantitative descriptive and qualitative techniques. Findings show a significant need for interactive multimedia applications in guidance and counseling services. The CareCouns prototype includes features such as Guidelines, Home, Text, Video, X P5, Counselor, and Evo. The application was validated with material validity at 90% and media at 94%, and rated practical by teachers at 94% and students at 98%. The CareCouns application is effective as a counseling media tool to enhance understanding of free association and the values of Pancasila Student Profiles.